Fortune's mystery woman - Leigh, Allison (Fortunes of Texas. Fortune's secret children, 2024)
"When wealthy rancher Ridge Fortune stumbles upon a woman injured in his stable, he's stunned. Why is Hope Marks in Chatelaine...with a baby in her arms and fear in her heart? When he realizes she's hiding from a mysterious couple circling her beloved baby girl, Ridge rushes to her aid--even as he resists his attraction to this woman he cannot have. She could be married. Or have even more secrets. As Hope begins to recover her memories, perhaps Ridge can help her find her way to escape her past...and step into a future that begins in his arms." -- Page [4] cover.